DISIPLIN PEGAWAIPERUSAHAAN DAERAH AIR MINUM(PDAM) KOTA PONTIANAK - Wargo Toyetno E.21109072 (FISIP Universitas Tanjungpura, 2013)
The problem in this research is a violation of hours worked by employees known as 705, ie the employees come to the office and absent at 7.00 pm, but after missing the employee left the job without any official statement or command, and back again just to absent at 17.00 pm. This study aims to describe Director Policy Implementation Regional Water Company of discipline and punishment discipline with a qualitative approach. The research found that lack of employee understanding of the rules is a violation of discipline director, for example, came to the office late, not absent, in the office for more than a week in a row. Enforcement of disciplinary rules, especially the application of disciplinary sanctions for violations have not been implemented consistently, meaning there is no firmness of the management in the application of disciplinary sanctions for violations committed by employees. Addressing the phenomenon of communication is directed to enforcement of regulations disiplin.Hendaknya director of discipline and punishment discipline, socialized regularly and describes in detail the rules are often broken, the following consequences and informed employees through active discussions both formally and informally or with other words needed interactive socialization. Keywords: Regulation, Director, Discipline.